Audit Quality Audit Fee On Audit Risk - Ratu Munawarah; Enggar Diah Puspa Arum (International Journal of Economics, Business and Innovation Research, 2025)
This study is a Systematic Literature Review (SLR) of SINTA-indexed articles from 2023–2025 that discuss the relationship between audit quality, audit fees, and audit risk in Indonesia. Articles were collected through Google Scholar and the SINTA portal using selection and content analysis methods. The results indicate that audit fees have a positive effect on audit quality, but this relationship can change depending on the level of audit risk. Audit risk also acts as a moderating or mediating variable in improving audit effectiveness. This study highlights the limited number of studies that combine these three variables in a single research model.